Implementasi Pelayanan Administrasi Kependudukan Kota Malang - Wahyono, Suko; Prihatminingtyas, Budi; Purwatiningsih, Annisa (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2019)
Policy implementation is a government action in regulating and taking care of people’s needs in various affairs including fulfilling basic population services for the community. The purpose of this paper is to analyze the implementation of basic population services at the Malang City Population and Civil Registration Service. The research method using qualitative descriptive shows that the services of family cards and identity cards according to the Community Satisfaction Survey are very good results. Meanwhile the results of the implementation according to Edward III aspects of communication have gone well through the process of communication between the service staff and the community. Resource aspects experience barriers to human resources of high school graduates and some are elderly. The capacity of internet service networks is still not optimal and wasteful of the budget because all services are not online systems. The aspect of disposition, gives an attitude to the apparatus that with the provision of incentives and benefits they are able to carry out services that are not from the community. This is due to the formulation of this policy through the government institutions of the city of Malang so that they must be able to carry out their duties as well as possible. Aspects of the Bureaucratic Structure, provide Standard Operating Procedures (SOP) as guidelines for the duties and functions of the apparatus in serving the community. for this reason, good service is needed by paying attention to aspects of human resources and facilities that support the effectiveness of population services at the Malang City Population and Civil Registration Service Keywords: Implementation, Public Policy, Basic Population Services.